Costly Signals? : Democracy Aid Shocks and Political Repression, 1981-2013 - Scott, James; Hernandez, Allegra (The Age of Human Rights Journal, 2021)
Developed states increasingly turned to democracy assistance strategies as the Cold War came to an end. A number of recent studies conclude that such aid positively affected democratization in recipients. But, like foreign aid, democracy assistance allocations are subject to change, sometimes dramatically. In foreign aid, sudden, sizable reductions – or aid shocks (e.g., Nielsen et al. 2011) – can have severe consequences, precipitating conflict in the recipient state. How do democracy aid shocks affect recipient states? This analysis examines the effects of sudden withdrawals of democracy aid – or democracy aid shocks – by the U.S. on recipient regime behavior, specifically, their treatment of citizens and civil society groups. We argue that democracy aid shocks trigger repressive action by recipients resulting in harmful human rights practices by the regime. Examining U.S. democracy aid to the developing world from 1982-2013, we find that, after controlling for other relevant factors likely to affect the human rights practices of a regime, democracy aid shocks are associated with subsequent repression of human rights in the recipient state. Our analysis thus sheds light on an external factor affecting human rights practices within states, as well as an important element of the consequences of democracy aid decisions. We conclude by assessing the implications for democracy promotion strategies and human rights behavior.